2018
DOI: 10.1039/c8cc06966b
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the isomeric heterogeneity of glycans: ion mobility separations in structures for lossless ion manipulations

Abstract: To address the challenges associated with glycan analyses, we have implemented a structures for lossless ion manipulations (SLIM) serpentine ultra-long path with extended routing (SUPER) ion mobility-mass spectrometry (i.e. SLIM SUPER IM-MS) platform to achieve much higher resolution of isomeric glycoforms. We have demonstrated the potential of this platform as a future component of the glycomics toolbox.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
123
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(135 citation statements)
references
References 42 publications
12
123
0
Order By: Relevance
“…IMS of glycans. In analogy to bimodal distributions in LC chromatograms that are often reported for glycans, ion mobility arrival time distributions (ATDs) can also exhibit multiple features that were speculated to originate from the respective a and b anomers [30,45,51,52], however, identification of the two anomeric forms has remained elusive. In the present study we investigated a set of roughly 20 different sodiated glycans ranging from small mono-and disaccharides to larger oligosaccharides using our ultrahigh-resolution IMS instrument, a subset of which is displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IMS of glycans. In analogy to bimodal distributions in LC chromatograms that are often reported for glycans, ion mobility arrival time distributions (ATDs) can also exhibit multiple features that were speculated to originate from the respective a and b anomers [30,45,51,52], however, identification of the two anomeric forms has remained elusive. In the present study we investigated a set of roughly 20 different sodiated glycans ranging from small mono-and disaccharides to larger oligosaccharides using our ultrahigh-resolution IMS instrument, a subset of which is displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We clearly observe additional small peaks that correspond to ions having slightly different three-dimensional structure from the major species. Multiple peaks in the ATD could correspond to different isomers (e.g., α and ÎČ anomers at the reducing end OH 15,17,25 ) or to multiple conformers of those isomers. There can also be different protonation sites or different sites to which fucose might migrate.…”
Section: Resultsmentioning
confidence: 99%
“…Mass spectrometry (MS)based strategies are widely used in glycan analysis because of their speed and sensitivity, [6][7][8][9] and various kinds of chromatographic, electrophoretic, and ion mobility (IM) separations are often employed in combination with MS to more fully resolve different isomeric forms. 6,[10][11][12][13][14][15][16][17] Recently, spectroscopy-based methods have been combined with MS to tackle the issue of glycan identification. [18][19][20][21][22][23][24][25][26][27][28] For relatively large and complex molecules such as N-linked glycans, cryogenic spectroscopy is best suited to distinguishing the subtle structural differences between isomers.…”
Section: Introductionmentioning
confidence: 99%
“…It is yet to be established whether all reducing carbohydrates are resolvable into three (or more [26]) components. If so, a very specific carbohydrate identification workflow could be based on the combination of the m / z value of the precursor and product ion, their CCS values, and their relative abundance.…”
Section: Discussionmentioning
confidence: 99%
“…This was a clue that those product ions exhibiting the difference had retained the reducing end of the saccharide and thus contained anomeric information—a structural difference responsible for the separation of precursors [25]. A further study by Nagy et al showed that carbohydrates containing the reducing end can exhibit two (or more) features in IM spectra, while non-reducing carbohydrates presented as a single peak [26]. The above studies hint that high-resolution IMS could resolve the anomeric forms of sodiated carbohydrates; however, sodium coordination itself could play a major role in this phenomenon.…”
Section: Introductionmentioning
confidence: 99%